Communication, latéralité et cerveau chez les primates humains et non humains : vers une origine gestuelle ou multimodale du langage ? - Adrien Meguerditchian; Hélène Cochet; Catherine Wallez; Jacques Vauclair (Revue de Primatologie)
Most language functions are under the dominance of the left cerebral hemisphere and involve a complex neural network in which some cerebral regions play a key-role such as Broca’s and Wernicke's areas within the frontal and the temporal lobes respectively. Thus, the question of the lateralization and the localization of the neural substrate involved in gestural and vocal communication in nonhuman primates is essential for evaluating the potential continuities with such hemispheric specialization for language and thus for determining the best candidate for direct precursors of speech. In the present paper, after emphasising the tight relation between gestures and language in human infants, we underlie the specific significance of communicative gestures and of the progressive control of the oro-facial system and the vocal tract in the course of the language evolution by reviewing the findings related to lateralization and brain correlates of both vocal and gestural systems in nonhuman primates.